2014
DOI: 10.2989/16085906.2014.961937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an exercise programme with people living with HIV: research in a disadvantaged setting

Abstract: This study aimed to analyse the physical health effects of a community based 10-week physical activity programme with people living with HIV. It was developed, implemented and evaluated in a disadvantaged community in South Africa. A pre-post research design was chosen. Major recruitment and adherence challenges resulted in a small sample. Among the 23 participants who took part in both baseline and final testing, compliant participants (n = 12) were compared to non-compliant participants (n = 11). Immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
1
11
0
4
Order By: Relevance
“…While the majority of studies investigating the effects of exercise on PLHIV have been conducted in developed countries, in recent years there have been isolated studies of this type emanating from the developing world, conducted in low and middle-income countries (LMICs) (Mutimura et al 2008a;Mutimura et al 2008b;Ley et al 2014;). Globally, most published studies on exercise for PLHIV have focused on interventions conducted in health care institutions or recreational facilities (for example hospitals or gymnasiums).…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of studies investigating the effects of exercise on PLHIV have been conducted in developed countries, in recent years there have been isolated studies of this type emanating from the developing world, conducted in low and middle-income countries (LMICs) (Mutimura et al 2008a;Mutimura et al 2008b;Ley et al 2014;). Globally, most published studies on exercise for PLHIV have focused on interventions conducted in health care institutions or recreational facilities (for example hospitals or gymnasiums).…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, low-intensity activities and moderate activities such as aerobic exercise with warm-up, work-out and cool-down stages have been advocated as the most appropriate [30][31][32][33][34][35]. In some studies that implemented high-intensity exercise, the dropout rate was high, or a lot of participants could not meet the recommended level of performance [35,36]. The study by Pillay et al [35] also highlighted the importance of not only considering the duration of the exercise but also the volume and intensity.…”
Section: Tools and Resources Currently Used To Support Pamentioning
confidence: 99%
“…Frequency refers to how often an individual engages in an activity, usually the number of days per week [56]. Most HIV studies have used a three times weekly intervention for both the aerobic exercise (AE) and progressive resistive exercise (PRE) component [12,13,57] with success three/four times per week [31], a few studies have reported positive results twice weekly [39,58]. Table 3 indicates the specific frequency of the AE and PRE component according to the different clinical categories with the corresponding CD4 cell count for each category [55]; for example, HIV-infected individuals in clinical category A1 (asymptomatic, acute HIV, or persistent generalized lymphadenopathy with ≥500 cells/μL) ( Table 3) [55].…”
Section: Frequencymentioning
confidence: 99%
“…A combination of aerobic and progressive resistive exercise (CARE) appears to be more effective than applying only one component [10]. Research studies have shown an improvement in and other measures of fitness [3,10,13], functional capacity [10,14], improvement in body composition (decreases in fat percentage, increases in abdominal fat loss, BMI, and lean body mass) [8,13,57], increases in viral load and cell counts for TCD4+/ TCD8 [13], improvement in QOL [8,9,11] and mood state [61], as well as improvement in lipid profile [13] and glucose tolerance [21].…”
Section: Combined Aerobic and Resistive Exercise (Care)mentioning
confidence: 99%